2023
DOI: 10.3390/medicina59020237
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Implants Retaining Removable Partial Dentures in Subjects without Posterior Teeth: A 5-Year Prospective Study Comparing the Maxilla and the Mandible

Abstract: Background and objectives: Long-term studies of clinical outcomes of mini-implants (MDIs) in the first premolar/canine sites retaining a bilateral free-ending removable partial dentures (RPD) in Kennedy class I subjects have not been well documented. The aim was to assess clinical outcomes in a prospective 5-year cohort study comparing the mandible and maxilla. Material and Methods: Participants (n = 92) who received two MDIs each and a new RPD were reviewed after one, three and five years. A total of 71 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…The results were statistically evaluated standard deviation and p value was calculated and data was statistically significant. As per studies the ideal ISQ score ranged from 56-83, the values in our study ranged in this range [15][16] . The ISQ score of patients that had two implants was 68.5±4.3, whereas the patients who went through 3 implants had ISQ score as 72.1±4.5.…”
Section: Discussionsupporting
confidence: 62%
“…The results were statistically evaluated standard deviation and p value was calculated and data was statistically significant. As per studies the ideal ISQ score ranged from 56-83, the values in our study ranged in this range [15][16] . The ISQ score of patients that had two implants was 68.5±4.3, whereas the patients who went through 3 implants had ISQ score as 72.1±4.5.…”
Section: Discussionsupporting
confidence: 62%
“…Even the insertion of only three MDIs in the mandible for complete OD retention showed very good outcomes in a five-year clinical study [15]. Insertion of two MDIs showed good survival rates and low amounts of marginal bone loss only when used for retention of removable partial dentures [16][17][18]. However, the clinical outcomes of only two MDIs retaining a complete mandibular OD are still doubtful [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Our 5-year study revealed less bone loss in both groups (−0.33 ± 0.27 mm in the three-MDI group and −0.36 ± 0.74 in the four-MDI group). The lower amount of peri-implant vertical bone loss recorded in the present study can be attributed to the fact that bone loss in the submerged MDIs around the polished surface was considered as bone remodeling [15,17,19]. Only a decrease in the bone below the roughened, threaded surface was considered as bone loss.…”
Section: Discussionmentioning
confidence: 55%
“…The fixed-type MDIs have proved to be successful in the retention of crowns or short bridges in the mandibular incisor region [17]. Furthermore, the insertion of two or more MDIs for the retention of partial removable dentures was also confirmed as a successful treatment modality [18][19][20].…”
Section: Introductionmentioning
confidence: 96%